"Beating the Bad Rap:" A Qualitative Study of Social Studies Educators Using Film. Issue 4 (3rd July 2020) - DeHart, Jason
Abstract: The film-based practices of four social studies teachers were examined using a qualitative methodology. The research interviewed teachers twice over a 2-month period, collected handouts, and collected audio-recorded teacher logs. Three of the teachers taught social studies primarily, while a fourth teacher was responsible for both English and social studies content. The findings indicate that teachers used film in addition to a wide range of other visual practices. Teachers used film actively rather than passively to facilitate dialogic connections, as well as elicit thinking about their content areas.